A Specific Circulating MicroRNA Cluster Is Associated to Late Differential Cardiac Response to Doxorubicin-Induced Cardiotoxicity In Vivo - Ruggeri, Clarissa; Gioffré, Sonia; Chiesa, Mattia; Buzzetti, Marta; Milano, Giuseppina; Scopece, Alessandro; Castiglioni, Laura; Pontremoli, Marta; Sironi, Luigi; Pompilio, Giulio; Colombo, Gualtiero I.; D’Alessandra, Yuri (Disease Markers, 2018)
Background. Cardiotoxicity is a detrimental side effect of the anticancer drug doxorubicin (DOX), characterized by progressive heart dysfunction. Circulating microRNAs (miRNAs) are recognized as potential biomarkers of cardiac disease; thus, we aimed to investigate their association with late cardiotoxicity in an animal model of disease. Methods. Twenty C57BL/6 female mice were administered with 24 mg/kg cumulative dose of DOX or saline during 2 weeks, followed by a recovery period of one month (T42). Echocardiography was performed at baseline and at T42, and plasma samples were collected at T42. The selection of all miRNAs of interest was conducted by literature overview and by screening, followed by RT-qPCR validation. Results. The analysis of cardiac function at T42 evidenced five DOX-treated animals indistinguishable (NoTox) from controls (CTRLs), while four presented heart impairment (Tox). Our analyses identified eight dysfunction-associated plasma miRNAs. In particular, seven miRNAs were found downregulated in comparison to CTRLs, miR-1-3p, miR-122-5p, miR-127-3p, miR-133a-3p, miR-215-5p, miR-455-3-p, and miR-499a-5p. Conversely, miR-34a-5p showed increased levels in Tox plasma samples. Noteworthy, we determined a cluster composed of miR-1-3p, miR-34a-5p, miR-133a-3p, and miR-499a-5p that distinguished with high-accuracy Tox from NoTox mice. Conclusion. This is the first study indicating that, similarly to what is observed in patients, DOX-administered animals present a differential cardiac response to treatment. Moreover, our results indicate the presence of specific plasma miRNAs whose expression reflect the presence of cardiac dysfunction in response to drug-induced injury.